Gender and the poetics of excess : moments of brocade - Ford, Karen Jackson (University Press of Mississippi, 1997)
The argument posed in this analysis is that the poetic excesses of several major female poets, excesses that have been typically regarded as flaws in their work, are strategies for escaping the inhibiting and sometimes inimical conventions too often imposed on women writers. The forms of excess vary with each poet, but by conceiving of poetic excess in relation to literary decorum, this study establishes a shared motivation for such a strategy. Literary decorum is one instrument a culture em-ploys to constrain its writers. Perhaps it is the most effective because it is the least definable. The.